Analisis Pengaruh Makroekonomi, Komoditas Dunia, dan Indeks Dunia terhadap Indeks Harga Saham Gabungan (IHSG) pada Periode 2014-2019 - Fadhil Ahmad (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research explains the influence of inflation, Exchange Rate, BI Rate, GDP, World Gold Price, Crude Oil Price, Dow Jones Industrial Average (DJIA), and Nikkei 225 toward Jakarta Composite Index (JCI). Type of research used in causality research with a quantitative approach. The sample was based on daily time series data from 1 January 2014 until 31 December 2019, using a complete sampling method that consists of 2190 samples. This research used a generalized autoregressive conditional heteroskedasticity (GARCH) method. The result of hypothesis testing by the GARCH method shows that the World Gold Price and Dow Jones Industrial Average significant have a positive effect, Then the Nikkei 225 significant have a negative effect, and then the Inflation, Exchange Rate, BI Rate, and GDP have not significant to the Jakarta Composite Index (JCI). The implication of this research provides information to investors who must pay attention to World Gold Price, Dow Jones Industrial Average, and Nikkei225 if they want to invest in Indonesian.